Pharmacoepigenomics: An Interplay of Epigenetic Modulation of Drug Response and Modulation of the Epigenome by Drugs - Mendiratta, Shweta; Jain, Shruti; Maini, Jayant; Brahmachari, Vani (Current Pharmaceutical Design, 2014)
Epigenetic modulation captures the lack of correlation between the genotype and the phenotype. It also provides an interface between environment and the genotype leading to functional plasticity of the genome. While drug response can be modulated by the epigenome, the therapeutic intervention by drugs can also be considered as an environmental cue for epigenetic alterations. The effect of genetic polymorphism has accrued considerable interest and population polymorphism leading to variation in drug response is being studied extensively. The available data on the epigenetic marking of the whole genome in different contexts implies that no biological pathway or process in the mammalian system is free of epigenetic influence and thus, drug metabolism would not be an exception. In the light of the fact that the epigenome is not only variable between individuals, but that it also varies between different tissues of the same individual and with the age of the individual, it is still a long journey to transit from the correlation to causal relationship between drug response and the epigenomic variations. The present review is focused on recent developments in the area and a brief discussion of the future prospects and challenges.
Keywords: cytochrome P450 isoforms